Theology and the (post)apartheid condition Genealogies and future directions - Venter, Rian (Theological Explorations, 2016)
Knowledge transmission and generation belong to the core mission of the public university. In democratic South Africa, the transformation of these processes and practices in higher education has become an urgent and contested task. The Faculty of Theology at the University of the Free State has already done some original work on the implications of these for theology. One area of investigation that has not yet received due attention concerns the role of theological disciplines, and especially the relation between academic disciplines and societal dynamics. This research project addresses the challenge and this volume reflects the intellectual endeavour of lectures, research fellows and a post-graduate student associated with the faculty. Each theological discipline has its own history and has already experienced reconstruction, both globally and in South Africa. Some of these genealogical developments and re-envisioning are mapped by the contributions in this volume. The critical questions addressed are: what are the contours of the (post)apartheid condition and what are the implications for responsible disciplinary practices in theology? The chapters convey an impression of the vitality of theology at the University of the Free State and in South Africa and give expression to fundamental shifts that have taken place in theological disciplines, and also of future tasks. This research project aims to stimulate reflection on responsible and innovative disciplinary practices of theology in South Africa, which, we envisage, will contribute to social justice and human flourishing. -Rian Venter, University of the Free State